Guidelines for Identification and Management of Plant Disease Problems: Part II. Diagnosing Plant Diseases Caused by Fungi, Bacteria and Viruses - Ken Pernezny; Monica Elliott; Aaron Palmateer; Nikol Havranek (EDIS)
PP248/MG441- PP251/MG444, a 4-part series by Aaron Palmateer, Ken Pernezny, Monica Elliott, and Nikol Havranek, are new additions to the Master Gardener Handbook. They provide beginning Master Gardener volunteers with methods for taking a systematic approach to diagnosis of plant disease problems. Published by the UF Department of Plant Pathology, February 2008.